Determinan price earnings ratio dan stock return (studi kasus pada perusahaan manufaktur yang terdaftar di bursa efek Indonesia periode 2009-2013) (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
ABSTRACT Anggraini, 2016, the purpose of the research was to determinan price earnings ratio and stock return. This research aims at investigating of the influence of the companys fundamental variables,comparising financial leverage, dividend payout ratio, and return on equity on the price earnings ratio, and the influence of the companys fundamental factors and the price earnings ratio on the stock return. The population of this study is companys at Indonesia Stock Exchange period 2009-2013. Sample technique used is obtained by used purposive sampling method, using the criteria, a total of 38 companies were selected. Data sources used secondary data. The method of analysis was the path analysis. The result of the research indicate that the influence of financial leverage negative and significant, the influence of dividend payout ratio positive and significant, the influence of return on equity negative and no significant on the price earnings ratio. The influence of financial leverage negative and no significant, the influence of return on equity positive and significant, the influence of price earnings rationegatif and no significant on the stock return.Keyword: financial leverage, dividend payout ratio, return on equity, price earnings ratio and stock return.